196k views
1 vote
(x^3-5x^2)+(2x-10)Find all 0's

User PSKP
by
5.7k points

1 Answer

4 votes

Given:


\mleft(x^3-5x^2\mright)+\mleft(2x-10\mright)

You can find all its zeros, as follows:

1. Make the expression equal to zero:


(x^3-5x^2)+(2x-10)=0

2. Distribute the positive sign. Remember the Sign Rules for Multiplication:


\begin{gathered} +\cdot+=+ \\ -\cdot-=- \\ +\cdot-=- \\ -\cdot+=- \end{gathered}

Then:


x^3-5x^2+2x-10=0

3. Factor the expression:

- Make two groups using parentheses:


(x^3-5x^2)+(2x-10)=0

- Identify the Greatest Common Factor of each group. For the first group:


GCF=x^2

And for the second group:


GCF=2

- Factor them out:


x^2(x^{}-5^{})+2(x-5)=0

4. Notice that this expression is common in both terms:


x-5

Then, you can factor it out:


(x-5)(x^2+2)=0

5. Now you can set up these two equations:


\begin{gathered} x-5=0\text{ (Equation 1)} \\ \\ x^2+2=0\text{ (Equation 2)} \end{gathered}

6. Solve for "x" from each equation:

- For Equation 1:


x_1=5_{}

- For Equation 2:


\begin{gathered} x^2=-2 \\ x_{}=\pm\sqrt[]{-2} \end{gathered}

By definition:


\sqrt[]{-1}=i

Then, you get:


x=\pm\sqrt[]{-2}\Rightarrow\begin{cases}x_2=i\sqrt[]{2} \\ \\ x_3=-i\sqrt[]{2}\end{cases}_{}

Hence, the answer is:


\begin{gathered} x_1=5_{} \\ \\ x_2=i\sqrt[]{2} \\ \\ x_3=-i\sqrt[]{2} \end{gathered}

User Rico Suter
by
5.0k points